Effect of timing, technique and molecular features on brain control with local therapies in oncogene-driven lung cancer - El-Shafie, Rami; Seidensaal, Katharina; Bozorgmehr, Farastuk; Kazdal, Daniel; Eichkorn, Tanja; Elshiaty, Mariam; Weber, D.; Allgäuer, Michael; König, Laila; Uzun-Lang, Kristin; Forster, Tobias; Arians, Nathalie; et al. (ESMO open, 2021)
Background - The improved efficacy of tyrosine kinase inhibitors (TKI) mandates reappraisal of local therapy (LT) for brain metastases (BM) of oncogene-driven non-small-cell lung cancer (NSCLC). - Patients and methods - This study included all epidermal growth factor receptor-mutated (EGFR+, n = 108) and anaplastic lymphoma kinase-rearranged (ALK+, n = 33) TKI-naive NSCLC patients diagnosed with BM in the Thoraxklinik Heidelberg between 2009 and 2019. Eighty-seven patients (62%) received early LT, while 54 (38%) received delayed (n = 34; 24%) or no LT (n = 20; 14%). LT comprised stereotactic (SRT; n = 40; 34%) or whole-brain radiotherapy (WBRT; n = 77; 66%), while neurosurgical resection was carried out in 19 cases. - Results - Median overall survival (OS) was 49.1 months for ALK+ and 19.5 months for EGFR+ patients (P = 0.001), with similar median intracranial progression-free survival (icPFS) (15.7 versus 14.0 months, respectively; P = 0.80). Despite the larger and more symptomatic BM (P < 0.001) of patients undergoing early LT, these experienced longer icPFS [hazard ratio (HR) 0.52; P = 0.024], but not OS (HR 1.63; P = 0.12), regardless of the radiotherapy technique (SRT versus WBRT) and number of lesions. High-risk oncogene variants, i.e. non-del19 EGFR mutations and ‘short’ EML4-ALK fusions (mainly variant 3, E6:A20), were associated with earlier intracranial progression (HR 2.97; P = 0.001). The longer icPFS with early LT was also evident in separate analyses of the EGFR+ and ALK+ subsets. - Conclusions - Despite preferential use for cases with poor prognostic factors, early LT prolongs the icPFS, but not OS, in TKI-treated EGFR+/ALK+ NSCLC. Considering the lack of survival benefit, and the neurocognitive effects of WBRT, patients presenting with polytopic BM may benefit from delaying radiotherapy, or from radiosurgery of multiple or selected lesions. For SRT candidates, the improved tumor control with earlier radiotherapy should be weighed against the potential toxicity and the enhanced intracranial activity of newer TKI. High-risk EGFR/ALK variants are associated with earlier intracranial failure and identify patients who could benefit from more aggressive management.
Gesehen am 13.08.2021